Technology as a Competitiveness Factor in Extensive Livestock Family Production Systems - Gómez Miller, Raúl; Ferreira de Mattos, Gustavo (Agrociencia Uruguay, 2013)
65% of family farms have as their main activity livestock production systems (DIEA-MGAP 2008), therefore it is very important to evaluate the relevance of the research done by the National Agricultural Research Institute (INIA), the impact of its lines of work in livestock production, and the application level of these technologies in household production systems. This study examines the attention family farmer’s decision pay to technology within a radius of 40 kilometers from the city of Tacuarembó. The research analyzes the diversity of strategies that can be verified in the area, and how technical change is operating in a region that has undergone significant changes with the advent of new products and production systems. For properly achieving complementarity among techniques, which would allow a deeper approach to this subject, we used both quantitative and qualitative methodologies.The findings of this study show the diversity of situations, as well as the existence of a turning point in the evolution of family production systems, since the new context is generating uncertainty about their chances of survival. In this framework, the study examines the role of technology adoption as a factor of competitiveness.